Immunological response enhancement in cows with subclinical mastitis fed diet supplemented with Macleaya cordata - Khattab, Mostafa S. A.; Haiqiang, Li; Shaoxun, Tang; Qiongxian, Yan; Yong, Liu; Zhiliang, Tan; Qi, Lu (Frontiers in Veterinary Science, 2025)
IntroductionThe present study explored the immune response, milk production and health status of mastitis-infected lactating cows fed diets supplemented with Macleaya cordata extract.MethodsTwenty-four Holstein and Jersey cows were equally assigned to two experimental groups: the first group was fed a control diet (control), and the second experimental group was fed a control diet plus Macleaya extract at 8 g/head/d (Macleaya). The experiment was conducted for 60 days. The daily milk yield was recorded, and the milk samples were analyzed for total solids, fat, protein, and lactose contents.ResultsBlood samples were analyzed for different blood constituents, biochemical parameters, antioxidant capacity and immune indices. Compared with the control, the addition of Macleaya improved immune indices (p < 0.05). No significant differences (p > 0.05) were recorded between the two groups for different rumen liquor parameters, antioxidant capacities, milk yields or compositions. However, supplementing the diet with Macleaya significantly decreased SCC, SAA, and endotoxin.ConclusionThis study suggested that supplementing the diets of lactating cows with Macleaya extract potentially improved their immune competence without adversely impacting their productive performance.